Synchronous Microwave Ablation Combined With Cisplatin Intratumoral Chemotherapy for Large Non-Small Cell Lung Cancer - Huang, Guanghui; Li, Wenhong; Meng, Min; Ni, Yang; Han, Xiaoying; Wang, Jiao; Zou, Zhigeng; Zhang, Tiehong; Dai, Jianjian; Wei, Zhigang; Yang, Xia; Ye, Xin (Frontiers in Oncology, 2022)
Background: Microwave ablation (MWA) and intratumoral chemotherapy (ITC) are useful for treating tumors in animal models; however, its clinical use in patients with large non‑small cell lung cancer (NSCLC) remains unknown. This retrospective study aimed to evaluate preliminary outcomes of MWA + ITC for large NSCLC. Methods: From November 2015 to April 2020, a total of 44 NSCLC patients with a mean lesion diameter of 6.1 ± 1.5 cm were enrolled and underwent synchronous MWA + ITC procedures. The primary endpoint was local progression-free survival (LPFS); secondary endpoints were progression-free survival (PFS), complications, overall survival (OS) and associated prognostic factors. Results: The median follow-up time was 19.0 months. At the 1 month CT scan, complete tumor ablation was observed in 47.7% of cases. Median LPFS was 12.1 months; 1-, 2-, and 3-year LPFS rates were 51.2%, 27.9%, and 13.6%, respectively. A shorter LPFS was significantly associated with large lesions (HR 1.23, 95% CI 1.02–1.49; p = 0.032). Median PFS was 8.1 months; 1-, 2-, and 3-year PFS rates were 29.5%, 18.2%, and 9.1%, respectively. LPFS was significantly superior to PFS (p = 0.046). Median OS was 18.8 months. The 1-, 2-, 3-, and 5-year OS rates were 65.9%, 43.2%, 26.4%, and 10.0%, respectively. In univariate comparisons, high performance status (PS) score, smoking, and larger lesions were significantly correlated with poor survival. In multivariate analysis, advanced age, higher PS score, higher stage, larger lesion, and prior systematic treatment were independent prognostic factors for shorter OS. Adverse events were well tolerated and all patients recovered after appropriate intervention. Conclusions: MWA + ITC is a safe and effective new modality of local treatment for large NSCLC and can significantly prolong LPFS.